The Effect of Work Culture on Visitor Satisfaction at PDIKM (Minangkabau Cultural Documentation and Information Center) - Mansyuri, M. Rodi; Khaidir, Afriva (Science and Environmental Journal for Postgraduate, 2020)
The purpose of this study was to examine the effect of work culture on visitor satisfaction at PDIKM Padang Panjang City. This study uses a quantitative approach. The study population was tourists visiting PDIKM Padang Panjang City. The sample in this study consisted of 376 respondents who were determined using the Slovin formula with an error rate of 5% and the sampling technique was done through accidental sampling. Data analysis techniques using simple regression analysis. The findings show that there is a significant influence between work culture on visitor satisfaction by 13.8%. The results of the study concluded that work culture influences visitor satisfaction at PDIKM Padang Panjang City.